The nesting of the Pink-eared Duck - Warham, John (Wildfowl, 1957)
1. An account is given of the nesting of the Pink-eared Duck (Malacorhynchus membranaceus) in a swamp at Moora, Western Australia, during 1956. 2. Nests were in holes or crotches in trees and lined solely with down, which is unusually oily, clings to itself and appears to be a most efficient insulator. 3. Both sexes swim to the nesting site at the beginning of an incubation spell, but it is unknown whether both incubate. 4. The birds perch readily and climb sloping limbs without difficulty. 5. Adults use three calls: a disyllabic whistle serves as a flight note and alarm; a rattling cry is associated with success after territorial disputes; a soft purring note used on approaching the nest and at the time of hatching probably serves as an integration note once the chicks are on the water. 6. Distress and contentment notes are given by the newly hatched chick. 7. After hatching, the young are induced to descend by the calls of both parent birds circling in the water below the nest site. 8. During inter- and intra-specific threat displays neck and head are stretched along the surface towards the antagonist and the beak opened and closed. The presumed female is very aggressive at the time of hatching.